Olfactory learning. - Davis, R.L. (Neuron, 2004)
The olfactory nervous systems of insects and mammals exhibit many similarities, suggesting that the mechanisms for olfactory learning may be shared. Neural correlates of olfactory memory are distributed among many neurons within the olfactory nervous system. Perceptual olfactory learning may be mediated by alterations in the odorant receptive fields of second and/or third order olfactory neurons, and by increases in the coherency of activity among ensembles of second order neurons. Operant olfactory conditioning is associated with an increase in the coherent population activity of these neurons. Olfactory classical conditioning increases the odor responsiveness and synaptic activity of second and perhaps third order neurons. Operant and classical conditioning both produce an increased responsiveness to conditioned odors in neurons of the basolateral amygdala. Molecular genetic studies of olfactory learning in Drosophila have revealed numerous molecules that function within the third order olfactory neurons for normal olfactory learning.